2016
DOI: 10.1109/tcst.2015.2422796
|View full text |Cite
|
Sign up to set email alerts
|

Discrete-Time Reduced-Complexity Youla Parameterization for Dual-Input Single-Output Systems

Abstract: A controller design is presented for directly shaping the sensitivity function in the feedback control of dual-input single-output (DISO) systems. We provide special forms of discrete-time Youla-Kucera (YK) parameterization to obtain stabilizing controllers for DISO systems, and discuss concepts to achieve a reduced-complexity formulation. The proposed YK parameterization is based on an inverse of the loop transfer function, which gives benefits such as clearer design intuition and reduced complexity in constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Glaria and Goodwin presented a simple parameterisation for the class of all stabilising controllers for linear minimum phase plants [29]. It was shown that this result was the dual of the well‐known Youla parameterisation [30, 31]. Morari and Zafiriou provided a parameterisation, based on which a systematic method was developed for H2 optimal controller design [32].…”
Section: Introductionmentioning
confidence: 99%
“…Glaria and Goodwin presented a simple parameterisation for the class of all stabilising controllers for linear minimum phase plants [29]. It was shown that this result was the dual of the well‐known Youla parameterisation [30, 31]. Morari and Zafiriou provided a parameterisation, based on which a systematic method was developed for H2 optimal controller design [32].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we propose an AFC design method tailored for achieving precise repetitive motion in DISO systems. The previous control scheme implements the AFC to entire control loop [13], [14], [15]. The parameters of AFC are designed to the open loop characteristics summing up the that of course actuator and fine actuator.…”
mentioning
confidence: 99%
“…θ ai is designed based on the previous control scheme[13],48[14]. The block diagram is described as shown in Fig.7, where49 L lp = P lp C lp denotes the open loop of lower piezo actuator, 50 VOLUME 11, 2023…”
mentioning
confidence: 99%